1990
DOI: 10.1164/ajrccm/142.5.1129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inflammatory Mediators on the Responsiveness of Isolated Human Airways to Methacholine

Abstract: Several studies have suggested that in asthmatics the quantities of inflammatory mediators such as histamine, thromboxane A2 (TxA2), prostaglandin D2 (PGD2), prostaglandin F2 alpha (PGF2 alpha), and leukotriene C4 (LTC4) that are present in the airway lumen are related to the degree of bronchial responsiveness to inhaled methacholine (MCh). Therefore, we studied the effect of these mediators on the cholinergic responsiveness of isolated human airway segments. Lung tissue collected at thoracotomy from 30 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The inflammatory mediators prostaglandin (PG) D2 and thromboxanes have a variety ofeffects on target cells in the airways, which may be relevant in the etiology of asthma. PGD2 induces a pronounced contraction of human airway smooth muscle and increases the bronchial sensitivity (43,45,46). This is supported by evidence that PGD2 is released in vivo in the human lower respiratory tract after acute allergic challenge (47).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The inflammatory mediators prostaglandin (PG) D2 and thromboxanes have a variety ofeffects on target cells in the airways, which may be relevant in the etiology of asthma. PGD2 induces a pronounced contraction of human airway smooth muscle and increases the bronchial sensitivity (43,45,46). This is supported by evidence that PGD2 is released in vivo in the human lower respiratory tract after acute allergic challenge (47).…”
Section: Resultsmentioning
confidence: 83%
“…Other TP receptor subtypes may exist, which could explain why the TP receptor is not very selective; however, strong evidence supports the existence of a single form of the TP receptor in both platelets and smooth muscle cells (5). Receptor binding is suggested as contributing actively to the pathogenesis of bronchial asthma (7,45,46).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the EC50 of 3 mM for histamine-induced bronchoconstriction in human PCLS matches that in human tracheal preparations [28]. The EC50 value for methacholine-induced bronchoconstriction in human PCLS was 0.4 mM compared with 1 mM in isolated human bronchi [29]. This difference may be explained by the observation from rat PCLS that smaller airways are more sensitive to methacholine [14].…”
Section: The Model Of Precision-cut Lung Slicesmentioning
confidence: 82%
“…Compared to MCH challenge, the ratio of AEdyn/AHiPl was in the same order as during histamine aerosol inhala tion [4], In allergic asthmatics an increased bronchial reponsiveness after allergen provocation tests was found, de pending on inflammatory reactions in the airway walls [6]. Several studies showed a correlation between concen trations of inflammatory mediators such as histamine, thromboxane A2, prostaglandin D2, prostaglandin F2a and leukotriene C4 in the tracheal lumen and the degree of bronchial responsiveness [2,26], Different mediators could be shown to interact and modify bronchial re sponses to single agonists [2,3,[27][28][29].…”
Section: Discussionmentioning
confidence: 97%